Cell-Free DNA Promotes Inflammation in Patients With Oral Lichen Planus via the STING Pathway - Deng, Jing; Pan, Weiyi; Ji, Ning; Liu, Na; Chen, Qian; Chen, Jinhuan; Sun, Yutong; Xie, Liang; Chen, Qianming (Frontiers in Immunology, 2022)
Background Damaged and dead cells release cell-free DNA (cfDNA) that activates cyclic GMP–AMP (cGAMP) synthase (cGAS), which leads to the activation of stimulator of interferon genes (STING) via the second messenger cGAMP. STING promotes the production of inflammatory cytokines and type I interferons to induce an inflammatory response. Oral lichen planus (OLP), a chronic autoimmune disease involving oral mucosa characterized by the apoptosis of keratinocytes mediated by T-lymphocytes, is related to the activation of multiple inflammatory signaling pathways. Currently, the relationship between cfDNA and OLP has not been confirmed. We hypothesized that cfDNA may be a potential therapeutic target for OLP. Methods cfDNA was extracted from the saliva and plasma of OLP patients; its concentration was measured using the Quanti-iT-PicoGree kit and its relationship with OLP inflammation was assessed. cfDNA of OLP patients (cfDNA-OLP) was transfected into THP-1 macrophages and the expression of inflammatory factors was investigated by performing quantitative real time PCR (qRT-PCR), western blotting, and enzyme-linked immunosorbent assay (ELISA). STING expression was analyzed in the tissues of OLP patients and healthy controls using immunohistochemical staining and western blotting. siRNA was used to knockdown STING expression in THP-1 macrophages, and the inflammatory cytokines tumor necrosis factor-α (TNF-α) and interleukin-6 (IL-6) secreted by cells following cfDNA-OLP transfection were detected using ELISA. Finally, the effect of the cationic polymer PAMAM-G3 was evaluated on the treatment of inflammation induced by cfDNA-OLP. Results The concentration of cfDNA in the saliva and plasma of OLP patients was considerably higher than that of healthy controls, and it positively correlated with the levels of inflammatory cytokines and clinical characteristics. cfDNA-OLP induced an inflammatory response in THP-1 macrophages. STING expression was significantly higher in OLP tissues than in the gingival tissues of healthy controls. STING knockdown suppressed cfDNA-OLP-induced inflammation in THP-1 macrophages. PAMAM-G3 inhibited the inflammatory response caused by cfDNA-OLP. Conclusion The cfDNA level is increased in OLP patients, and the STING pathway activated by cfDNA-OLP might play a critical role in OLP pathogenesis. Treatment with PAMAM-G3 reduced the inflammation induced by cfDNA-OLP, and therefore, may be a potential treatment strategy for OLP.